2015
DOI: 10.1108/rpj-11-2013-0119
|View full text |Cite
|
Sign up to set email alerts
|

Development of an electrospinning-based rapid prototyping for scaffold fabrication

Abstract: Purpose -This paper aims to present the development of an electrospinning-based rapid prototyping (ESRP) technique for the fabrication of patterned scaffolds from fine fiber. Design/methodology/approach -This ESRP technique unifies rapid prototyping (RP) and electrospinning to obtain the ability of RP to create a controllable pattern and of electrospinning to create a continuous fine fiber. The technique follows RP process of fused deposition modeling, but instead of using extrusion process for fiber creation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Electrospinning techniques decrease jet instability and control deposition by adjusting the electrode setup, collecting fibers between fixed plates, or minimizing distance between spinneret and collector . However, significant decreases in throughput or disruption of fiber morphology can occur due to residual charge buildup, low collection speed, insufficient solvent evaporation, applied voltage, or polymer flow rate . A comparison of these techniques, along with other nanofiber fabrication systems, is further summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospinning techniques decrease jet instability and control deposition by adjusting the electrode setup, collecting fibers between fixed plates, or minimizing distance between spinneret and collector . However, significant decreases in throughput or disruption of fiber morphology can occur due to residual charge buildup, low collection speed, insufficient solvent evaporation, applied voltage, or polymer flow rate . A comparison of these techniques, along with other nanofiber fabrication systems, is further summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Once formed, the fibers can be collected and processed using external pumps, alternating applied electric fields, spinnerets, coagulation, and wash chambers, or heated drum rolls to form aligned functional materials . Several electrospinning techniques have been developed to further control fiber deposition and structure, producing aligned fibrous nanostructures by minimizing the distance between a charged nozzle and grounded collector . While these modifications enable geometries which were previously unattainable for electrospun fibers, the technique remains limited in both speed and the range of materials used.…”
Section: Introductionmentioning
confidence: 99%
“…Bu et al [30] developed a mechano-electrospinning technique for fabricating oriented nanofibres and the controlled parameter was the moving speed of the substrate. Chanthakulchan et al [31] developed an Electrospinning-based rapid prototyping method for fabrication of patterned scaffolds but only achieved a certain level, due to the challenges of controlling the vibration. Auyson et al [32] studied the effect of various parameters of the hybrid Electrospinning / Fused Depositio Modelling (FDM) on the fabricated scaffold and concluded that two most important parameters to get a continuous jet are the voltage applied and the standoff distance between the nozzle and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was demonstrated that ESRP‐fabricated three dimensional hierarchical scaffolds are effective tools for the expansion of HSCs without modifying their phenotype. It is anticipated that future advances and improvements in vibration suppression and fiber solidification will critically fortify the capability of the ESRP technique …”
Section: Physical Approachmentioning
confidence: 99%